The ambiguous role of healthcare providers: a new perspective in Human Resources Management - Panari, Chiara; Levati, W.; Bonini, A.; Tonelli, M.; Alfieri, E.; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2016)
Background and aim: A strategic Human Resources Management approach, that overcomes an administrative Personnel Management, is becoming crucial for hospital organizations. In this sense, the aim of this work was to examine the figure of healthcare provider using the concept of role, as expected behaviour in term of integration in the organizational culture. Method: The instrument used to analyse the healthcare provider figure was “role mapping”. Particularly, semistructured interviews were conducted and involved to 36 health professionals of four units in order to examine the behaviour expectations system towards the healthcare providers. Results: The analysis revealed that the expectations of different professionals related to the healthcare provider were dissimilar. Physicians’ expectations referred to technical preparation and efficiency, while nurses and nurse coordinators required collaboration in equip work and emotional support for patients. In all Operating Units, directors were perceived as missing persons with vague expectations of efficiency. Differences concerned also the four Units. For example, in intensive care Unit, the role of healthcare provider was clearer and this figure was perceived as essential for patients’ care and for the equip teamwork. On the contrary, in Recovery Unit the healthcare provider was underestimated, the role was ambiguous and not integrated in the equip even if there was a clear division of tasks between nurses and healthcare providers. Conclusion: The “role mapping” instrument allows to identify healthcare provider profile and find possible role ambiguity and conflicts in order to plan adequate human resources management interventions.